About the origin of retroviruses and the co-evolution of the gypsy retrovirus with the Drosophila flamenco host gene. - Pelisson, A.; Teysset, L.; Chalvet, F.; Kim, A.; Prud'homme, N.; Terzian, C.; Bucheton, A. (Genetica, 1997)
The gypsy element of Drosophila melanogaster is the first retrovirus identified so far in invertebrates. According to phylogenetic data, gypsy belongs to the same group as the Ty3 class of LTR-retrotransposons, which suggests that retroviruses evolved from this kind of retroelements before the radiation of vertebrates. There are other invertebrate retroelements that are also likely to be endogenous retroviruses because they share with gypsy some structural and functional retroviral-like characteristics. Gypsy is controlled by a Drosophila gene called flamenco, the restrictive alleles of which maintain the retrovirus in a repressed state. In permissive strains, functional gypsy elements transpose at high frequency and produce infective particles. Defective gypsy proviruses located in pericentromeric heterochromatin of all strains seem to be very old components of the genome of Drosophila melanogaster, which indicates that gypsy invaded this species, or an ancestor, a long time ago. At that time, Drosophila melanogaster presumably contained permissive alleles of the flamenco gene. One can imagine that the species survived to the increase of genetic load caused by the retroviral invasion because restrictive alleles of flamenco were selected. The characterization of a retrovirus in Drosophila, one of the most advanced model organisms for molecular genetics, provides us with an exceptional clue to study how a species can resist a retroviral invasion.